Tokamachi, Niigata, Japan Experience Sharing on Preparation Towards Active Ageing, 2020 - Wong Chin Mun; Diana Safraa Selimin; Mohd Rohaizat Hassan; Rozita Hod; Azmawati Mohammed Nawi; Norfazilah Ahmad Norfazilah Ahmad; Mohammad Saffree Jeffree; Syed Sharizman Syed Abdul Rahim; Zamberi Sekawi; Tg Aizan Hamid; Noriah Hajib; Norhaslira Abdul Rahim (UKM, 2021)
As the year 2020 marked a significant milestone to our country with regards to our vision to become a developed country, the UKM-Niigata University âExchange Program & Seminar on Program for Enhancing Health Policies for Healthy and Active Aging In-Comparison Between Malaysia & Japanâ was suitably conducted. The MOU between UKM-NU (Niigata University) since year 2009 has opened plenty of opportunities for various fruitful collaborations in terms of knowledge, research and experience sharing between both countries. This round, the opportunity was offered to two post graduate DrPH (Doctor of Public Health) students, together with professors, associate professors and senior officers from Department of Community Health, Faculty of Medicine UKM, Faculty of Medicine & Health Sciences UMS and UPM, MyAgeing UPM and Cheras District Health Office. The Malaysian delegation was led by Associate Professor Dr. Mohd Rohaizat bin Hassan.